STRATEGI PENGEMBANGAN KELEMBAGAAN KOPERASI PERTANIAN JERUK PAMELO DI DESA TAMBAKMAS, KECAMATAN SUKOMORO, KABUPATEN MAGETAN - Wijaya, Riko Setya; Wiyatiningsih, Sri; Harijani, Wiwik Sri; Sentoso, Wahyu (Berkala Ilmiah AGRIDEVINA, 2019)
The success of the integrated agribusiness system of a commodity must be followed by an increase in farmers' bargaining position, as well as common problems encountered in Tambakmas Village, Sukomoro District, Magetan Regency as the Jeruk Pamelo production center. The development of the Pamelo orange plant has several problems, namely having a weak position and not being able to improve the bargaining position of farmers because it is still in the form of a social institution (ie a farmer group), and has not yet become a socioeconomic institution (cooperative). In many countries, farmer cooperatives not only increase production, productivity and product quality, but also lead to an increase in the welfare and quality of life of their members. This study specifically aims to develop the Jeruk Pamelo farmer cooperative in Tambakmas Village, Sukomoro District, Magetan Regency. This study uses a SWOT analysis used to formulate a strategy, followed by a mapping of strategies to develop a Pamelo orange farmer cooperative in accordance with its character. This method is because the population to be studied is quite large, namely 150 people. The number of samples used in this study was 30 people. The results showed that based on the overall SWOT Analysis, Gapoktan institutional development was in Cell / Quadrant I. In that position the appropriate strategy was Growth Strategy, then the Grand Strategy could be formulated as follows: Formation of Pamelo Orange Cooperative, Pamelo orange agro-tourism development, Capital development farmer groups, and FOBIO development of Pamelo oranges.DOI : https://doi.org/10.33005/adv.v8i2.1931